Efficiency, Equality, and Labeling: An Experimental Investigation of Focal Points in Explicit Bargaining - Isoni, Andrea; Poulsen, Anders; Sugden, Robert; Tsutsui, Kei (American Economic Review, 2014)
We investigate Schelling's hypothesis that payoff-irrelevant labels (“cues”) can influence the outcomes of bargaining games with communication. In our experimental games, players negotiate over the division of a surplus by claiming valuable objects that have payoff-irrelevant spatial locations. Negotiation occurs in continuous time, constrained by a deadline. In some games, spatial cues are opposed to principles of equality or efficiency. We find a strong tendency for players to agree on efficient and minimally unequal payoff divisions, even if spatial cues suggest otherwise. But if there are two such divisions, cues are often used to select between them, inducing distributional effects. (JEL C78, D63, D83)